Antimicrobial metal-based thiophene derived compounds - Shakeela Yasmeen; Sajjad Hussain Sumrra; Muhammad Safwan Akram; Zahid H. Chohan (Taylor & Francis Group, 2017)
A novel series of thiophene derived Schiff bases and their transition metal- [Co(II), Cu(II), Zn(II), Ni(II)] based compounds are reported. The Schiff bases act as tridentate ligands toward metal ions via azomethine-N, deprotonated-N of ammine substituents and S-atom of thienyl moiety. The synthesized ligands along with their metal complexes were screened for their in vitro antibacterial activity against six bacterial pathogens (Escherichia coli, Shigella flexneri, Pseudomonas aeruginosa, Salmonella typhi, Staphylococcus aureus and Bacillus subtilis) and for antifungal activity against six fungal pathogens (Trichophytonlongifusus, Candida albicans, Aspergillus flavus, Microsporum canis, Fusarium solani and Candida glabrata). The results of antimicrobial studies revealed the free ligands to possess potential activity which significantly increased upon chelation.